2015
DOI: 10.3855/jidc.5032
|View full text |Cite
|
Sign up to set email alerts
|

A case of imported neurocysticercosis in Portugal

Abstract: Neurocysticercosis (NCC) is the most common cause of acquired epilepsy in resource-poor countries. We report the case of a 24-year-old woman born and residing in Guinea-Bissau, who was transferred to Portugal two months after the onset of a possible meningitis (fever, headache, seizures, and coma) that did not respond to antibiotic treatment. The diagnosis of NCC was confirmed by MR imaging, which showed multiple lesions compatible with cysticercus, and by polymerase chain reaction (PCR) of the cerebrospinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Other helminthic parasites, whose eggs or larvae can sometimes be localized within the CNS, may elicit an eosinophilic pleocytosis. These include cerebral and spinal cord schistosomiasis, as Schistosomal myelopathy occurred relatively frequently in Malawi (Naus et al, 2003), toxocariasis canis or visceral larva migrans (Robinson et al, 2002), trichinellosis (Nikolić et al, 1988), echinococcosis caused a meningeal hydatid cyst (Bottieau et al, 2003), neurocysticercosis (Valadas et al, 2015), fascioliasis (Arjona et al, 1995), cerebral paragonimiasis (Xia et al, 2015) and Pypen et al (2015) reported a rare case of Strongyloides stercoralis meningitis in an immunocompromised patient treated for a lung carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Other helminthic parasites, whose eggs or larvae can sometimes be localized within the CNS, may elicit an eosinophilic pleocytosis. These include cerebral and spinal cord schistosomiasis, as Schistosomal myelopathy occurred relatively frequently in Malawi (Naus et al, 2003), toxocariasis canis or visceral larva migrans (Robinson et al, 2002), trichinellosis (Nikolić et al, 1988), echinococcosis caused a meningeal hydatid cyst (Bottieau et al, 2003), neurocysticercosis (Valadas et al, 2015), fascioliasis (Arjona et al, 1995), cerebral paragonimiasis (Xia et al, 2015) and Pypen et al (2015) reported a rare case of Strongyloides stercoralis meningitis in an immunocompromised patient treated for a lung carcinoma.…”
Section: Introductionmentioning
confidence: 99%